2010
DOI: 10.3732/ajb.1000125
|View full text |Cite
|
Sign up to set email alerts
|

The impact of altered precipitation variability on annual weed species

Abstract: Our results suggest that changes in precipitation variability likely will affect the composition and relative abundance of agriculturally important weeds. These results are important for understanding how changes in the temporal variability of precipitation due to global climate changes could impact plants in non-arid communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…In the context of global climate change, the precipitation pattern may be variable and result in more water supply heterogeneity, which is a considerable challenge faced by terrestrial ecosystems [10, 11, 12]. Longer periods between rainfall events and a tendency for lower precipitation during summer are expected in some regions [13, 14], such as northern China.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of global climate change, the precipitation pattern may be variable and result in more water supply heterogeneity, which is a considerable challenge faced by terrestrial ecosystems [10, 11, 12]. Longer periods between rainfall events and a tendency for lower precipitation during summer are expected in some regions [13, 14], such as northern China.…”
Section: Introductionmentioning
confidence: 99%
“…Climate change involves rising temperatures Gillett et al 2011) and altered precipitation patterns, which also increase the probability for summer droughts in Europe (Bloomfield et al 2006;Lobell and Burke 2008;Robinson and Gross 2010). Weeds are influenced by these altered abiotic conditions (Dukes et al 2009;Singer et al 2013).…”
Section: Direct Effects Of Climate Change On Weedsmentioning
confidence: 99%
“…Robinson and Gross studied how increased variability in precipitation would impact two common annual weeds in the USA, Chenopodium album and Setaria faberi Herrm. (giant foxtail) [126]. As might be expected, the impact of periodic droughts varied, depending on plant life stage, but overall, Chenopodium album showed greater resilience under prolonged dry periods than Setaria faberi.…”
Section: Responses To Increased Climate Variabilitymentioning
confidence: 77%
“…As might be expected, the impact of periodic droughts varied, depending on plant life stage, but overall, Chenopodium album showed greater resilience under prolonged dry periods than Setaria faberi. The authors concluded that predicted changes in the occurrence and severity of precipitation events are likely to alter relative abundances of agriculturally important weeds [126].…”
Section: Responses To Increased Climate Variabilitymentioning
confidence: 99%
See 1 more Smart Citation